Small-scale river flow hydropower: design, IoT monitoring, and field validation - Tengku Azlan Shah, Tengku Atiqah Farhana; Markom, Arni Munira; Yusof, Yusrina (Universiti Teknologi MARA, Sarawak, 2026)
Hydroelectric energy represents a sustainable and reliable power source for off-grid and remote areas, particularly in environments where conventional electricity access is limited and solar energy performance is reduced by dense vegetation. This study addresses the need for a portable, small-scale hydroelectric solution by developing and validating a lightweight IoT-enabled micro-hydroelectric generator designed to operate in low-head, densely vegetated stream environments. The proposed system integrates a compact micro-hydro turbine with an ESP32 microcontroller and a multi-sensor suite, including water flow, voltage, and current sensors, enabling real-time performance monitoring via the Blynk mobile platform. The novelty of this work lies in the integration of a fully portable form factor with IoT-based real-time monitoring, allowing rapid field deployment and performance evaluation without permanent infrastructure, which distinguishes it from conventional fixed micro-hydro systems. Field evaluation conducted over a 30-minute period indicates that the voltage and current generally increase with operating time, reaching peak values of 10.03 V and 22.29 mA at the 25-minute mark, corresponding to a maximum power output of 224 mW. The observed trends suggest stable energy generation under natural river flow conditions, with minor variations attributed to environmental factors such as flow fluctuations. Overall, the results demonstrate the practical feasibility of the proposed system as a portable off-grid energy solution for rural, outdoor, and emergency applications.